Good Pharmacovigilance Practice in the United States and the European Union - V. A. Merkulov; N. D. Bunyatyan; A. P. Pereverzev (Безопасность и риск фармакотерапии)
The article presents the results of a comparative analysis of Goodpharmacovigilance practices (GVP), developed by experts of the regulatory bodiesof the European Union (EU) and the United States. It is shown that the EU GVP cover almost all possible aspects of pharmacovigilance. It is noted that the disadvantages of EU GVP are difficulties in the correct understanding and interpretation of certain definitions and processes, as well as the complexity of the implementation in practice of a number of provisions, mainly related to the organization of the quality management system, including audit and inspection. As the basis for development of the Russian Rules GVP is recommended to use the GVP EU